The spatial effects of the household's food insecurity levels in Ethiopia: by ordinal geo-additive model - Wubetie, Habtamu T.; Zewotir, Temesgen; Mitku, Aweke A.; Dessie, Zelalem G. (Frontiers in Nutrition, 2024)
Background: Food insecurity and vulnerability in Ethiopia are historical problems due to natural and human made disasters, which cover most of the areas at a higher magnitude with adverse effects on the healthy state of households. In Ethiopia, the problem is wider with higher magnitude, and this geographical distribution has not yet been investigated for the effects of cultures and shocks, despite previous case studies' suggestions on the effects of shocks and some other factors. The objective is to assess the geographic distribution of corrected-food-insecurity levels across zones and explore the comprehensive effects of diverse factors on each level of a household's food insecurity. Method: This study analyzed three-term household'-based panel data for years 2012, 2014, and 2016 with a total sample size of 11505 covering the whole regional states of the country. An extended additive model with empirical Bayes estimation by modeling structured spatial effect using Markov random field or tensor product and unstructured effect using Gaussian was adopted to assess the spatial distribution of FCSL across zones and to further explore the comprehensive effect of geographic, environmental, and socio-economic factors on the locally adjusted measure. Result: Despite a chronological decline, a substantial portion of Ethiopian households remains food-insecure (25%) and vulnerable (27.08%). The Markov random field model is a best fit based on Generalized cross-validation which explained 90.04% of the total variation by its spatial effects. Most of the northern and southwestern areas, and most of the south-east and north-west areas are hot spots of food insecurity and vulnerable areas of the country, respectively. Conclusion: Chronically food-insecure zones showed a strong cluster in the northern and southwestern parts of the country, even if higher levels of household food-insecurity in Ethiopia have shown a declining trend over the years. Therefore, in these areas, acting as interventions on spatial structure factors mainly zone level urbanization, education, early marriage control, and job creation side-to-side controlling conflict and drought effect by food aid and selected coping strategies, and performing integrated farming by conserving land and the environment of zones can help to reduce a household's probability of being on higher food-insecurity levels.